PENERAPAN MEDIA PEMBELAJARAN BERBASIS ANDROID DENGAN SAC UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS VI SD - Rafika Dian Rahmawati; Sri Wahyuni; Laikha Listiyani; Ummie Masrurah; Efri Roziaty; Kurniawan, Bayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Technological advancements require teachers to create learning media that align with technological progress and the demands of the times for students. One educational tool that meets the technological demands of modern science education is the Android-based Smart Apps Creator (SAC). SAC proves highly effective for developing specialized educational applications, particularly for the diverse subject of Natural Sciences at the elementary level. This research aims to evaluate the effectiveness of Android-based learning media using SAC in enhancing the science learning outcomes of sixth-grade students, focusing on the human locomotor system. Descriptive statistical analysis was employed as the research method. The findings indicate an improvement in students' learning outcomes regarding human locomotion, with the average pre-test score rising from 62.04 to 84.43 in the post-test. Furthermore, SAC facilitates the creation of educational media, eliminating the need for proficiency in programming languages.